The Glutaminase-1 Inhibitor [11C-carbony]BPTES: Synthesis and Positron Emission Tomography Study in Mice - Yiding Zhang; Katsushi Kumata; Lin Xie; Yusuke Kurihara; Masanao Ogawa; Tomomi Kokufuta; Nobuki Nengaki; Ming-Rong Zhang (MDPI AG, 2023)
Bis-2-(5-phenylacetamido-1,3,4-thiadiazol-2-yl)ethyl sulfide (BPTES) is a selective inhibitor of glutaminase-1 (GLS1), consequently inhibiting glutaminolysis. BPTES is known for its potent antitumor activity and plays a significant role in senescent cell removal. In this study, we synthesized [11C-carbonyl]BPTES ([11C]BPTES) as a positron emission tomography (PET) probe for the first time and assessed its biodistribution in mice using PET. [11C]BPTES was synthesized by the reaction of an amine precursor () with [11C-carbonyl]phenylacetyl acid anhydride ([11C]2), which was prepared from [11C]CO2 and benzyl magnesium chloride, followed by in situ treatment with isobutyl chloroformate. The decay-corrected isolated radiochemical yield of [11C]BPTES was 9.5% (based on [11C]CO2) during a synthesis time of 40 min. A PET study with [11C]BPTES showed high uptake levels of radioactivity in the liver, kidney, and small intestine of mice.